2011
DOI: 10.1590/s1679-62252011000300013
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the Pimelodus maculatus (Lacépède, 1803) embryogenesis (Siluriformes: Pimelodidae)

Abstract: The fish embryonic development comprises the events between the egg fertilization up to larvae hatching, being useful for the identification of viable eggs in productivity and survival studies as well as in raising experiments of several species. The goal of the present study was to characterize the embryonic development of Pimelodus maculatus (Siluriformes; Pimelodidae). The embryogenesis was typical of teleosteans, but with differences in relation to other species such as duration of development, type of bla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 25 publications
(37 reference statements)
4
46
0
Order By: Relevance
“…C,D, and A,B,C). It is also thin in P. maculatus during segmentation (Buzollo et al, ). The YSL characteristics that will remain quite constant till the 3–4 dpf or even later are establiahed at the 14‐somite stage when the yolk extension is formed (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C,D, and A,B,C). It is also thin in P. maculatus during segmentation (Buzollo et al, ). The YSL characteristics that will remain quite constant till the 3–4 dpf or even later are establiahed at the 14‐somite stage when the yolk extension is formed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The ultrastructure of the YSL has been described in the embryos of Fundulus heteroclitus (before and during epiboly; Lentz and Trinkaus, ; Trinkaus and Lentz, ; Bailey, ; Betchaku and Trinkaus, ), Oryzias latipes (up to hatching; Yamamoto, ; Kageyama, ), Perca fluviatilis (up to hatching; Krieger and Fleig, ), Prochilodus lineatus (up to hatching; Ninhaus‐Silveira et al, ), Pimelodus maculatus (up to hatching; Buzollo et al, ), Sebastes schlegeli (at the stage that corresponds to prehatching in F. heteroclitus; Shimizu and Yamada, ), in embryos (from the establishment of «vitelline» vascular system) and in the larvae of Salmo gairdneri (Vernier and Sire , b; Sire et al, ) and in the larvae of Salmo trutta morpha fario, Hippoglossus hippoglossus, Gadus morhua, Dicentrarchus labrax, Stizostedion lucioperca, Sparus aurata, Scophthalmus maximus, Pleuronectes platessa, Osteoglossum bicirrhosum (Walzer and Schönenberger, 1979a,b; Kjørsvik and Reiersen, ; Morrison, ; Mani‐Ponset et al, ; Poupard, 2000; Skjarven et al, ; Jaroszewska and Dabrowski, ). The developmental histology of the YSL has been studied in the embryos of Oncorhynchus keta (Nishida, ,b), in the larvae of Salmo irideus, O. keta, Hypomesus olidus, Leuciscus idus , S. lucioperca (Yamada, , b; Ostaszewska et al, ; Ostaszewska, ) and in both embryos with yolk sac and larvae of P. fluviatilis , Pterophyllum scalare and Coregonus alpinus (Kunz, ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we identified the embryonic and larval development stages according to the descriptions established for other Siluriformes studied so far (Cardoso et al, 1995;Buzollo et al, 2011) and also by Nakatani et al (2001) and Richards (2006).…”
Section: Terminology For Embryonic Developmentmentioning
confidence: 99%
“…Pseudoplatystoma fasciatum (Leonardo et al, 2004), Pseudoplatystoma corruscans (Campos, 2005), Rhamdia quelen (Baldisseroto & Neto, 2005), Pimelodus maculatus (Buzollo et al, 2011), Pauliceia luetkeni, and Iheringichthys labrosus . Furthermore, reproductive status of broodstock when reared under different rearing systems and hormonal treatment (hormone stimulation techniques to induce ovulation and spermiation) of Pimelodidae species were also described (Batlouni et al, 2006;Andrade et al, 2010;Romagosa, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Post-hatching development of Siluriformes has deserved many studies which illustrate a wide variety of developmental adaptation strategies, from species without true larval phases (lima et al, 2012) to other exhibiting many post-hatching phases, similar to the species of our study, as shown in the cascadu, Hoplosternum littorale (Hanckock, 1828) by ramnarine et al (1994). Taking into account exclusively the Pimelodidae family, a great variety of developmental stages, phase names and incubation times can be found, including hatching times as short as 14-16 h as reported by Buzollo et al (2011) andnogueira et al (2012), 30 h (Pereira et al, 2006), 50 h (honJi et al, 2012 and extremely prolonged incubations, as found in some marine catfishes (lima et al, 2012). It is generally accepted that in most teleosts, larger eggs will produce, as a rule, larger larvae with larger yolk sacs and therefore, more developed organisms at hatching (sanches et al, 1999).…”
Section: Discussionmentioning
confidence: 99%